Relationship between Loneliness and Interpersonal Relationships - Moore, Joseph A. (Canadian Journal of Counselling and Psychotherapy, 2012)
The study investigated Sullivan's view that loneliness is related to the type of childhood friends and activities and Zilboorg's view that lonely adults are more hostile in interpersonal situations. A sample of 88 female college students filled in a loneliness questionnaire, Leary's Interpersonal Check List, and answered questions about childhood friends. The hostility hypothesis was confirmed and the friendship hypothesis partially confirmed. The more lonely Ss were significantly more hostile-submissive. The findings suggest that a person's own behavior is an enduring mode of interaction responsible for bringing about, perpetuating, aggravating, and/or solving loneliness feelings.